Distribution and habitat preference of Bombus (Kallobombus) soroeensis (Fabricius, 1777) on the territory of Arkhangelsk Region - Potapov, GS; Kolosova, YuS (Arctic Environmental Research, 2018)
In this paper, we summarise material pertaining to the distribution and habitat preference of Bombus (Kallobombus) soroeensis (Fabricius, 1777) on the territory of Arkhangelsk Region. B. soroeensis is widely represented on the territory as nominative subspecies B. soroeensis ssp. soroeensis, which is common mainly in Fennoscandia, the British Isles and Eastern Europe. The northern border of the species range in the Arkhangelsk Region is the lower reaches of the Mezen River, located in the transition zone between the northern taiga and the forest-tundra. This locality is probably one of the most northern records of this species in the northern part of the Russian Plain. In Eastern Fennoscandia, B. soroeensis is distributed far to the north, i.e., in the northern parts of Finland and Norway. In relation to the habitat preference, B. soroeensis in the study region belongs to the category of meadow species. This species is typical of different types of meadows and ruderal habitats. B. soroeensis is not typical with regards to the native taiga habitats, in most cases. This is similar to the situation on the territory of Finland, where this species is associated with open meadow habitats. Individuals of B. soroeensis have been recorded on a wide range of entomophilous plants, and the main examples are Rhinanthus minor, Epilobium angustifolium, Cirsium arvense, Scorzoneroides autumnalis, Lotus corniculatus.